Occupational asthma in the salmon processing industry: a case series - Lauritzen, Hilde Brun; Fagernæs, Carl Fredrik; Tøndell, Anders; Hassel, Erlend; Tjalvin, Gro; Bang, Berit Elisabeth; Nordhammer, Anna Beathe Overn; Rodal, Liv Bjerke; Svedahl, Sindre Rabben; Slåstad, Siri (Occupational and Environmental Medicine, 2024)
Objectives - Exposure to bioaerosols in salmon processing workers is associated with occupational asthma. IgE-mediated allergy and other disease mechanisms may be involved in airway inflammation and obstruction. Knowledge about disease burden, mechanisms, phenotypes and occupational exposure is limited. Methods - Salmon processing workers referred to our occupational medicine clinic from 2019 to 2024 were included in a patient register. They were investigated in line with current guidelines for the management of occupational asthma, categorised according to diagnostic certainty and characterised with a focus on symptoms, work tasks and clinical findings. Results - A total of 36 patients were included, among whom 27 had typical symptoms of work-related asthma, and 21 were diagnosed with occupational asthma. Among those with occupational asthma, all worked in the filleting or slaughtering area at the time of symptom onset. Median latency from the start of exposure to symptom onset was 4 years. 14 (67%) of the patients with occupational asthma were sensitised to salmon. Three patients were sensitised to salmon skin but not salmon meat. Conclusions - Occupational asthma among salmon processing workers displays a heterogeneous clinical picture. IgE-mediated inhalation allergy towards various parts of the salmon seems to represent an important pathophysiological mechanism. However, some have occupational asthma with negative allergy tests. A comprehensive workup strategy including early initiation of serial peak expiratory flow and skin prick tests with various parts of the salmon should be considered. Although the incidence remains unknown, the substantial number of cases presented warrant increased efforts to reduce harmful exposure in the salmon processing industry.